Creativity of De-Ka kopertis X canteen empowerment through various oyster mushroom processing - Suryani; Yuliesi; Gusnayetti; Emi Handrina; Nurhaida; Susilastri; Desriana (Peneliti Teknologi Teknik Indonesia, 2021)
The De-Ka Kopertis X Canteen is one of the businesses that was just opened in April 2021 by the KPN Kopertis X cooperative management for the period 2021-2023. Previously this cooperative was only engaged in the savings and loan business, although this cooperative was founded in 1992. The canteen Business (Kantin DeKa) serves members in terms of providing breakfast and lunch for members who work in the LLDIKTI X office, as well as guests who are underweight. at the LLDIKTI X office. Apart from providing lunch and breakfast, there are also various snacks, such as fried foods and other cakes. There are only a few types of fried foods, so the canteen's income is less. The purpose of this service program is to empower the canteen with creativity in various processing of oyster mushrooms. The methods are Socialization about various processed snacks of oyster mushrooms, especially Crispy oyster mushrooms and oyster mushroom Rissoles. Workshop/training on making Crispy and Oyster Mushroom Rissoles. Assistance for canteen employees in making these various mushroom snacks until they become skilled. The result at the time of socialization increased partners' knowledge of oyster mushrooms and their processing, which was marked by an increase in post-test results of 90% from the average pre-test value of 21.4%. The increase in the income of the De-ka canteen per day is approximately Rp. 312,000. The manager's creativity-by processing oyster mushrooms into various snacks is an effort to empower De-Ka canteen to increase income.